From Operaismo to (Post)Operaismo: The Importance of the Cross with French Post-Structuralism - Gómez Villar, Antonio (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The aim of this article is to highlight the importance of French post-structuralism in the transition from operaismo to (post)operaismo [«workerism» to «post-workerism»]. The meeting between the French and Italian movements was not so much a project to unite the two schools of thought, but a process to reveal earlier resonances. What paved the way to a meeting between the movements were the deep theoretical ties that existed before the contingency of such a meeting. The outcome of that meeting cannot be reduced to a unit. This article explores it through the cracks and fissures of its sprawling, disruptive forms.